Comparison of Some of Pragmatic Skills between 4 to 6 Years Old Farsi Speaking Hard of Hearing Children with Normal Hearing Peers - Mehdi Rahgozar; Najva Mousavi; Sima-Shirazi; Akbar Daroubi; Maryam Danaye-Tousi; Abbas Pourshahbaz (University of Social Welfare and Rehabilitation Sciences, 2009)
Objective: Pragmatics is the study of speech acts and social aspects of communicative interactions in context. Hearing-impaired children suffer from language impairments due to lack of hearing sense which has important role in developing language skills. The purpose of this study is comparison of some of pragmatic skills including topic maintenance, turn-taking and repairs between 4 to 6 year-old Farsi speaking hard of hearing children with normal hearing peers. Materials & Methods: In this cross-sectional and case-control research, twenty one normal hearing children were chosen by simple random sampling method from ordinary kindergartens and twenty one hard of hearing children (71-95 db) were selected from deaf rehabilitation centers and speech therapy clinics of Tehran and Karaj by simple sampling method. The children of both groups were assessed by nonverbal intelligence subtests. If they did not show any difficulties, the pragmatic skills of them (topic maintenance, turn-taking and repair) were evaluated by researcher made tasks which their content validity was confirmed by a linguistic and two speech and language pathologists and reliability of them was determined by test-retest (0.70)<r </r <rResults: There were significant differences between two groups in duration of topic maintenance (P<0.001), scores of turn-talking (P<0.001), repairs in form of reply to request for clarification (P=0.003) and request for clarification (P=0.002). </r <rConclusion: The pragmatic abilities of hearing-impaired children were Significantly lower than those of normal hearing. <r </r</r